(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
As globalization is changing rapidly, knowing and understanding English has become more important and necessary than in past decades. English is a powerful communication bridge that connects people in various fields, such as business, science, and education, across nations. Therefore, the demand for English proficiency is high, and creative teaching methods could be a good solution to meet this request. This article analyzes innovative approaches to teaching English and explores useful methods for improving the quality of knowledge among students.